Experiences of drought, heavy rains, and flooding and linkages with refugee youth sexual and reproductive health in a humanitarian setting in Uganda: qualitative insights - C. H. Logie; M. Loutet; F. MacKenzie; M. Okumu; R. Leggett; F. S. Akinwande; S. Odong Lukone; N. Kisubi; P. Kyambadde; L. Otika; M. Lukwago; M. Narasimhan (Global Public Health)
Climate-related extreme weather events (EWE) exacerbate resource insecurities that, in turn, shape sexual and reproductive health (SRH). Refugee settlements face increased EWE exposure yet are understudied in EWE research. We explored experiences of climate change and SRH among refugee youth aged 16–24 in Bidi Bidi Refugee Settlement, Uganda. This qualitative study involved walk-along individual youth interviews and key informant (KI) service provider interviews. We conducted thematic analysis informed by the resource scarcity framework, which explores socioeconomic and ecological risks for resource insecurity. Participants (N = 44) included youth (n = 32; mean age: 20.0, standard deviation [SD]: 2.4; 50% men, 50% women) and KI (n = 12; mean age: 37.0, SD: 5.8; 75% men, 25% women). Findings illustrate how EWE shape SRH outcomes for refugee young women: (1) climate change contributes to water scarcity, extreme heat, and changing rain patterns; (2) drought contributes to resource scarcities (e.g. food, water) that increase sexual and gender-based violence (SGBV) risks, transactional sex, and menstruation insecurity and (3) heavy rains/flooding contribute to resource scarcities that increase SGBV risks, and sanitation insecurity exacerbates menstruation insecurity. Findings highlight how EWE-related resource insecurities are associated with poor SRH (STI/HIV acquisition risks, unplanned pregnancy, SGBV) and should be addressed in multi-level climate-informed humanitarian programmes.